Multiple bilateral oncocytomas of the native kidneys following renal transplantation: report of a rare case and review of the literature - Vernadakis, Spyridon (BioMed Central, 2013)
Renal oncocytomas are benign tumors of the kidneys, which are usually diagnosed postoperatively, due to differential diagnostic problems, from a sample of a renal cell carcinoma. The development of a renal oncocytoma in the native kidneys following renal transplantation is a very rare condition and only a few cases have been published in the world literature. In this case report we present a unique case of bilateral multifocal renal oncocytomas of the native kidneys in a female transplant recipient 6 years after renal transplantation. The patient’s postoperative clinical course was uneventful and no local recurrence or distant metastasis has been found so far. The pathology, clinical characteristics, and treatment of renal oncocytomas are also reviewed.